THE SOVEREIGNTY OF THE JURY VERDICT DOES NOT BAR VACATING THE DECISION THROUGH CRIMINAL REVIEW (CIPEEX, 2025)
This paper adopts a normative and case-law analysis to examine the compatibility between the sovereignty of jury verdicts and setting aside convictions by means of the criminal review action, specifying the prerequisites and limits of this extraordinary remedy so as not to infringe the Jury Court’s constitutional remit. It recognizes that sovereignty (Federal Constitution, art. 5, XXXVIII) is fundamental but not absolute, and that criminal review (Code of Criminal Procedure, art. 621) aims to correct miscarriages of justice after final judgment. Where new evidence of innocence, false evidence, a new fact, or manifest error is shown, review does not replace the jurors’ assessment; rather, it verifies serious defects and, if necessary, annuls the verdict so that a new jury trial may be held, thereby preserving sovereignty by resubmitting the case to jurors. Brazilian Supreme Court (STF) and Superior Court of Justice (STJ) case law has admitted such review without offending the principle, as it protects fundamental rights and the search for truth. It concludes that the legal system balances jury authority with the control of unjust convictions: criminal review may vacate the verdict and order a new trial when the decision is manifestly contrary to the evidence or tainted by serious error.
Keywords: jury court; sovereignty of verdicts; criminal review; Fundamental rights